The potential role of iNKT cells in experimental allergic encephalitis and multiple sclerosis. (April 2014) - Roozbeh, Maryam; Mohammadpour, Hemn; Azizi, Gholamreza; Ghobadzadeh, Samira; Mirshafiey, Abbas
Abstract Multiple sclerosis (MS) is an autoimmune disorder associated with neurological signs and chronic inflammatory demyelination of the central nervous system (CNS). MS has been thought as Th1 (T helper) and Th17 cells mediated disease, but cells of the innate immune system play an important role both in the initiation and progression of MS. The invariant Natural Killer T (iNKT) cells are the unique innate lymphocytes subtype involved in inflammation and autoimmune disorders and secretes cytokines such as interferon gamma (IFN-γ), Interleukin (IL)-10, IL-4 and IL-13. A reduction in number or defect in function of iNKT cells has been associated with an increased prevalence of autoimmune disorders indicating that iNKT cells have an immune-regulatory role in autoimmune disorders. Also, the protective role of iNKT cells has been extensively studied in EAE and the results of these studies show that iNKT cells might be a target for therapeutic purposes, but needs more extensive studies of their biology. In this review, we will attempt to show the protective role of iNKT cells in the pathogenesis of EAE and human disease.